2021
DOI: 10.1038/s41467-021-23142-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DNA methylation on 3D genome structure

Abstract: Determining the effect of DNA methylation on chromatin structure and function in higher organisms is challenging due to the extreme complexity of epigenetic regulation. We studied a simpler model system, budding yeast, that lacks DNA methylation machinery making it a perfect model system to study the intrinsic role of DNA methylation in chromatin structure and function. We expressed the murine DNA methyltransferases in Saccharomyces cerevisiae and analyzed the correlation between DNA methylation, nucleosome po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 86 publications
1
53
0
Order By: Relevance
“…This analysis can further be expanded to include genome-wide epigenome patterns highlighting an important role of the DNA methylation in the maintenance of 3D genome regulation. Interestingly, DNA methylation was found to intrinsically modulate chromatin structure and function by increasing chromatin condensation in peri-centromeric regions, decreasing the overall DNA flexibility, and favoring the heterochromatin state [ 122 ]. Further, it has been shown that cancer-related methylation loss is associated with the deregulation of 3D genome organization leading to the disruption of the genome compartmentalization [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…This analysis can further be expanded to include genome-wide epigenome patterns highlighting an important role of the DNA methylation in the maintenance of 3D genome regulation. Interestingly, DNA methylation was found to intrinsically modulate chromatin structure and function by increasing chromatin condensation in peri-centromeric regions, decreasing the overall DNA flexibility, and favoring the heterochromatin state [ 122 ]. Further, it has been shown that cancer-related methylation loss is associated with the deregulation of 3D genome organization leading to the disruption of the genome compartmentalization [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…This shows that epigenetic diversity may contribute to the phenotypic plasticity in invasive species independent of genetic diversity. As a consequence of DNA methylation, chromatin compresses into heterochromatin at the transcription start site and hence reduces the gene activity and its transcription (Buitrago et al, 2021). The reduced DNA methylation observed in C. canadensis in the non-native range of Kashmir Himalaya might explain the increased expression of ABC transporter genes.…”
Section: Discussionmentioning
confidence: 99%
“…To establish the suitability of the produced Dnmt1 N1580A (further on Dnmt1-TOP-seq) libraries for epigenome studies, we looked at the genome-wide distribution of identified modified ll CpG sites along a range of genomic features. In protein-coding genes, the CpG modification profile showed a characteristic profile (Jung et al, 2017;Buitrago et al, 2021) with a sharp drop at TSSs followed by a gradual increase toward the 3 0 end of genes and a second drop around TTS (Figure 5B). In addition, long regulatory RNAs showed a similar but less pronounced modification profile, in agreement with their gene-like transcriptional status.…”
Section: Genome-wide Selective Tracking Of Dnmt1 Catalysis In Live Escsmentioning
confidence: 99%